The Impact of pH on Clostridioides difficile Sporulation and Physiology - Wetzel, Daniela (Appl Environ Microbiol, 2020)
Clostridioides difficile is a pathogenic bacterium that infects the human colon to cause diarrheal disease. Growth of the bacterium is known to be dependent on certain bile acids, oxygen levels, and nutrient availability in the intestine, but how the environmental pH can influence C. difficile is mostly unknown. Previous studies indicated that C. difficile modulates the intestinal pH, and prospective cohort studies have found a strong association between a more alkaline fecal pH and C. difficile infection. Based on these data, we hypothesized that C. difficile physiology can be affected by various pH conditions. In this study, we investigated the impact of a range of pH conditions on C. difficile to assess potential effects on growth, sporulation, motility, and toxin production in the strains 630Δerm and R20291. We observed pH-dependent differences in sporulation rate, spore morphology, and viability. Sporulation frequency was lowest under acidic conditions, and differences in cell morphology were apparent at low pH. In alkaline environments, C. difficile sporulation was greater for strain 630Δerm, whereas R20291 produced relatively high levels of spores in a broad range of pH conditions. Rapid changes in pH during exponential growth impacted sporulation similarly among the strains. Furthermore, we observed an increase in C. difficile motility with increases in pH, and strain-dependent differences in toxin production under acidic conditions. The data demonstrate that pH is an important parameter that affects C. difficile physiology and may reveal relevant insights into the growth and dissemination of this pathogen. IMPORTANCE Clostridioides difficile is an anaerobic bacterium that causes gastrointestinal disease. C. difficile forms dormant spores which can survive harsh environmental conditions, allowing their spread to new hosts. In this study, we determine how intestinally relevant pH conditions impact C. difficile physiology in the two divergent strains, 630Δerm and R20291. Our data demonstrate that low pH conditions reduce C. difficile growth, sporulation, and motility. However, toxin production and spore morphology were differentially impacted in the two strains at low pH. In addition, we observed that alkaline environments reduce C. difficile growth, but increase cell motility. When pH was adjusted rapidly during growth, we observed similar impacts on both strains. This study provides new insights into the phenotypic diversity of C. difficile grown under diverse pH conditions present in the intestinal tract, and demonstrates similarities and differences in the pH responses of different C. difficile isolates.